Freshwater Sponge Tubella variabilis Presents Richer Microbiota Than Marine Sponge Species - Laport, Marinella Silva; Pinheiro, Ulisses; Rachid, Caio Tavora Coelho da Costa (Frontiers in Microbiology, 2019)
Sponges can host diverse and abundant communities of microorganisms, which constitute an interesting source of bioactive compounds. Thus, to broaden our knowledge about the diversity of the microbiota that is found in freshwater sponges, the microbial community of Tubella variabilis was analyzed using culture-independent and culture-dependent approaches. Additionally, sponge-associated bacteria were compared with those living in the surrounding waters. Bacteria were also tested for antimicrobial production. Overall, the microbial composition identified comprises at least 44 phyla belonging mainly to Proteobacteria and low percentages of Bacteroidetes, Acidobacteria, and Verrucomicrobia. Alphaproteobacteria was the dominant class in T. variabilis while Betaproteobacteria was dominant in freshwater. Our data also revealed a high richness of bacteria in comparison to another freshwater sponge and 32 marine sponges. A global comparison of the structure of microbiota of different sponges showed that the main structuring factor may be the sponge environment, with T. variabilis and all freshwater sponges clustering together, and far away from the marine sponges. Bacterial strains from sponges and from freshwater were isolated and 163 morphotypes were phylogenetically identified. These belong to 26 genera, of which 12 were exclusively found in sponge samples and three only in freshwater. Inhibitory activities were also detected among 20-25% of the isolates from sponges and freshwater, respectively. This study presents new information on the composition of the microbial community found in freshwater sponges, which is diverse, abundant and distinct from some marine sponges. Moreover, the antimicrobial activity observed from the bacterial strains might play an important role in shaping microbial communities of the environment.